Surgical complications following ESIN for clavicular mid-shaft fractures do not limit functional or patient-perceived outcome. Issue 4 (April 2016) - Lechler, Philipp; Sturm, Sarah; Boese, Christoph Kolja; Bockmann, Benjamin; Schwarting, Tim; Ruchholtz, Steffen; Lahner, Matthias; Frink, Michael
Abstract: Elastic intramedullary nailing (ESIN) has been proposed as an alternative minimal-invasive method for the operative management of mid-shaft fractures of the clavicle. However, a relevant complication rate has been reported in previous cohorts. The present retrospective single-centre study aimed to analyse the complications following ESIN in adult patients with clavicular mid-shaft fractures (Allman type I) and their impact on functional and patient-perceived outcome measures. Results were compared to a control group receiving locking plate osteosynthesis. The clinical course and outcome of operatively managed patients with clavicular mid-shaft fractures were retrospectively analysed. Patients were assigned to group A (ESIN) and group B (plate fixation). Radiological, functional (Constant Murley Shoulder Outcome Score (CS), the Disabilities of the Arm, Shoulder and Hand (DASH) Score, the Oxford Shoulder Score (OSS)), and patient perceived aesthetic and clinical outcome were measured. A total of 47 (33 male, 14 female) operatively managed patients with a mean age of 26.7 ± 14.9 years and a follow up time of 38.1 ± 19.4 months were analysed. 36 patients were treated by ESIN (Group A), whereas 11 patients received open reduction and internal plate fixation (Group B). Patients were operatively treated with a mean delay of 7.4 ± 9.3 days (group A: 6.6 ± 8.7 days, group B: 10.2 ± 11.1 days, p  = 0.326) between trauma and the surgical index procedure. There were no significant differences in the functional (CS: p  = 0.338, DASH: p  = 0.247, OSS: p  = 0.434) and patient-perceived ( p  = 0.346) outcome measures between both groups. Surgical complications were noted in 14 patients (group A: 12, group B: 2) and non-union in 4 patients (group A: 3, group B: 1). There was no correlation between the recorded complications as assessed by the Clavien and Dindo classification and the functional as well as the patient-perceived outcome measures. Despite a relevant incidence rate of surgical complications, ESIN provides good to excellent functional and patient-perceived results in the treatment of clavicular mid-shaft fractures.